Biomechanical Evaluation of the Stabilizing Function of Three Atlantoaxial Implants Under Shear Loading: A Canine Cadaveric Study. Issue 8 (28th September 2015) - Riedinger, Benoit; Bürki, Alexander; Stahl, Christina; Howard, Judith; Forterre, Franck
Abstract : Objective: To compare the biomechanical properties of a ventral transarticular lag screw fixation technique, a new dorsal atlantoaxial instability (AAI) clamp, and a new ventral AAI hook plate under sagittal shear loading after transection of the ligaments of the atlantoaxial joint. Study Design: Cadaveric biomechanical study. Animals: Canine cadavers (n = 10). Materials and Methods: The occipitoatlantoaxial region of Beagles euthanatized for reasons unrelated to the study was prepared leaving only ligamentous structures and the joint capsules between the first 2 cervical vertebrae (C1 and C2). The atlanto‐occipital joints were stabilized with 2 transarticular diverging positive threaded K‐wires. The occipital bone and the caudal end of C2 were embedded in polymethylmethacrylate and loaded in shear to a force of 50 Newtons. The range of motion (ROM) and neutral zone (NZ) of the atlantoaxial joint were determined after 3 loading cycles with atlantoaxial ligaments intact, after ligament transection, and after fixation with each implant. The testing order of implants was randomly assigned. The implants tested last were subjected to failure testing. Results: All stabilization procedures decreased the ROM and NZ of the atlantoaxial joint compared to transected ligament specimens. Only stabilization with transarticular lag screws and ventral plates produced a significant reduction of ROM compare to intact specimens. Conclusion: Fixation with transarticular lag screws and a ventral hook plate was biomechanically similar and provided more rigidity compared to dorsal clamp fixation. Further load cycling to failure tests and clinical studies are required before making clinical recommendations.